OPERATORS IDEALS OF GENERALIZED MODULAR SPACES OF CESARO TYPE DEFINED BY WEIGHTED MEANS - Simsek, Necip; Karakaya, Vatan; Polat, Harun (EUDOXUS PRESS, LLC, 2015)
In this work, we investigate the ideal of all bounded linear operators between any arbitrary Banach spaces whose sequence of approximation numbers belong to the generalized modular spaces of Cesaro type defined by weighted means. Also, we show that the completeness of obtained operator ideals.
Keywords: Approximation numbers; operator ideal; generalized weighted mean; GEOMETRIC-PROPERTIES; SEQUENCE-SPACES; NUMBERS; Computer Science; Mathematics